Tipologi Pemilih Pemula pada Pilkada Jabar 2018: Studi tentang Tipe Pemilih dari Kalangan Remaja di Kabupaten Purwakarta - Rohendi Rohendi; Faisal Muzzamil (Jurnal Adhyasta Pemilu, 2021)
The dynamics and reality of the Beginner Voters in each General Election is an exciting and vital entity to study and research, including the study of the First Voters in Purwakarta Regency in the 2018 West Java (Jabar) Regional Head Election (Pilkada). Beginner Voters in the 2018 West Java Pilkada, this study aims to reveal and describe: (1) the reality of the 2018 West Java Pilkada in Purwakarta Regency; (2) Types of Beginner Voters for the 2018 West Java Regional Head Elections in Purwakarta Regency. This research employs a qualitative descriptive-analytic method that includes three data gathering techniques: interviews, documents, and group discussion forums. This research is based on the voter typology idea. Two fundamental discoveries were discovered in this study as a consequence of data analysis, namely: (1) the category of Beginner Voters in the 2018 West Java Regional Head Elections in Purwakarta Regency were voters aged 17-20 years; (2) The Type of Beginner Voters in the 2018 West Java Pilkada in Purwakarta is Rational Voters. The findings of this investigation lead to two suggestions: (1) To develop a theory about political studies among adolescents; (2) As a guide in conducting political campaign strategies and political education for youth.